Geochemical Characteristic of Amphibolites from Asind, District Bhilwara, Rajasthan, India - Thomas, H.; Vishwakarma, N. (Asian Journal of Chemistry, 2011)
Amphibolites are frequently observed in the medium to high grade metamorphic rocks of Asind of proterozoic age. These amphibolites are the results of the metamorphism of pre-existing mafic igneous rocks under medium to high grade P-T conditions and consist essentially of hornblende - plagioclase - garnet - clinopyroxene - epidote - iron oxide. Geochemically, these orthoamphibolites are tholeiitic, show association with non-orogenic environment and shift to sub alkaline derivatives with progressive differentiation. The absence of Nb anomaly and a low Th/ La ratio of amphibolites, indicate an asthenospheric or primitive mantle source without any supra subduction imprint or crustal contamination, severally limiting the continental tholeiite option. It is also clear that the parent magma for these rocks was highly evolved in nature. This paper records the geochemical characters and a probable origin of these amphibolites.